Monitoring ocular discomfort using a wrist-mounted electronic logger. Issue 5 (October 2020) - Read, Michael L.; Navascues-Cornago, Maria; Keir, Nancy; Maldonado-Codina, Carole; Morgan, Philip B.
Graphical abstract: Highlights: A wearable device was used to log episodes of discomfort during contact lens wear. The frequency and distribution of these episodes differed between the 2 study lenses. The frequency and intensity of events increased towards the end of lens wearing day. This technique allows a non-invasive real time assessment of comfort-related symptoms. This approach is a useful tool in furthering our understanding of ocular discomfort. Abstract: Purpose: To investigate ocular discomfort during contact lens wear using a wrist-mounted electronic 'lens awareness logger' (LAL). Methods: Thirty symptomatic contact lens wearers wore study contact lenses for three days. On the first two days, two lens types which are known to differ in end-of-day comfort (lens A: senofilcon A and lens B: balafilcon A), were worn as a matching pair (randomised order). On day three, a pair of lens B was worn. On each day, the participant used a LAL. On day one and two, the participant pressed a button on the LAL whenever they became aware of their lenses due to discomfort. On day three, the participant used a multiple click protocol (1 = mild awareness to 3 = severe awareness) to report discomfort. Results: LAL events were similar on days one and two (17.3 vs. 15.8 events per day). There were significantly more LAL events for lens B (21.6 events per day) in comparison with lens A (11.6 events per day) ( p = 0.006). The LAL event profile highlighted peaks in awareness following lens application and towards the end of the wearing cycle. Comparison of the LAL event profile for the two lens types showed significant differences in lens awareness, particularly in the first half of the wearing cycle. LAL events on day 3, showed a uniform distribution of single and double clicks through the day, but a marked peak in triple clicks in the last two hours of lens wear. Conclusion: The LAL was able to differentiate between the study lenses and demonstrated differences in their LAL event profiles. Lens awareness associated with discomfort appeared to increase not only in frequency, but also in intensity towards the end of the wearing cycle. The ability of the LAL to track lens awareness suggests it is likely to be a useful tool in furthering understanding of ocular discomfort.